Naming Systems And Socio-Ritual Functions Of Traditional Probolinggo Food: An Ethnoculinary Study - Yazid Farisy; Millatuz Zakiyah (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research aims to find out how the naming system and social-ritual functions of traditional foods in the Probolinggo area, so that people can know the reasons behind the naming and traditions of these foods. This type of research is descriptive qualitative using Abdul Chaer's theory of naming system and meaning. Data analysis techniques used (1) data reduction, (2) data analysis, (3) data classification, (4) data interpretation, and (5) conclusion. The results showed that almost all of Probolinggo's traditional foods are part of Pendalungan culture, an acculturation of Java and Madura. The naming system of traditional foods in Probolinggo tends to be simple, based on the way of serving, the sound when eaten, or the process of making, and has no special meaning in the name. Most of Probolinggo's traditional foods do not have significant social or ritual functions, with the exception of ketan kratok which serves as a marriage proposal (social) and wiwitan ritual offering (ritual). In addition to Javanese-Madurese acculturation, Pendalungan culture in Probolinggo is also influenced by Islam, seen in the naming and use of jenang grendul/tajin plokor to welcome Safar and jenang suro/tajin sorah for Muharram, where the term 'sorah' in Madurese comes from the mention of the month of Suro in the Javanese calendar based on the Hijri calendar.